Diamond drumhead crystals for X‐ray optics applications. Issue 4 (14th July 2016) - Kolodziej, Tomasz; Vodnala, Preeti; Terentyev, Sergey; Blank, Vladimir; Shvyd'ko, Yuri
Abstract : Numerous applications in X‐ray crystal optics and instrumentation require ultra‐thin perfect diamond single crystals, just a few micrometres to a few tens of micrometres thick, properly functioning under Bragg diffraction conditions. Reported here are the successful manufacture and characterization of diamond drumhead crystals, monolithic crystal structures composed of a thin membrane furnished with a surrounding solid collar, using picosecond laser milling. Abstract : Thin (<50 µm) and flawless diamond single crystals are essential for the realization of numerous advanced X‐ray optical devices at synchrotron radiation and free‐electron laser facilities. The fabrication and handling of such ultra‐thin components without introducing crystal damage and strain is a challenge. Drumhead crystals, monolithic crystal structures composed of a thin membrane furnished with a surrounding solid collar, are a solution ensuring mechanically stable strain‐free mounting of the membranes with efficient thermal transport. Diamond, being one of the hardest and most chemically inert materials, poses significant difficulties in fabrication. Reported here is the successful manufacture of diamond drumhead crystals in the [100] orientation using picosecond laser milling. Subsequent high‐temperature treatment appears to be crucial for the membranes to become defect free and unstrained, as revealed by X‐ray topography on examples of drumhead crystals with a 26 µm thick (1 mm in diameter) and a 47 µm thick (1.5 × 2.5 mm) membrane.